Do the engineering education institutions provide soft skills education? Views of South African engineering professionals - Munir, F. (South African Journal of Higher Education, 2021)
Engineering is a profession that utilises knowledge of mathematics and science in order to find solutions to multifaceted problems for the benefit of humans. The advancement of a knowledge-based economy within a globalised world means engineering education institutions are responsible for producing graduates who possess exceptional technical and soft skills. With the universities preferring to provide traditional education and the global corporations looking for versatile graduates, the question arises who is responsible for providing the soft skills education to engineering students of the 21st century. The present study explores qualitative and quantitative data from engineering professionals across South Africa to determine their views on the teaching of soft skills in the engineering curriculum at the engineering education institutions. The data revealed that the engineering professionals are not satisfied with their soft skills training at the educational institutions and would like more focus on such education. The study has implications for the engineering education institutions to balance technical knowledge with soft skills training in their curricula to meet the requirements of the industry. Such education should be incorporated across the board into their professional training. This will result in empowered graduates who are able to carve their own path to professional success